Management Strategies to Improve Medical Personnel Collaboration Skills (Qualitative Study at Arafah Anwar Medika Hospital) - Anas Yahya Abdullah; Purwadhi Purwadhi; Rinawati Rinawati (Sean Institute, 2026)
Collaboration among medical personnel is a crucial component in improving the quality of care and patient safety in healthcare facilities. This study aims to analyze management strategies that can enhance the collaborative capabilities of medical personnel at Arafah Anwar Medika Hospital. The study used a descriptive qualitative method through semi-structured interviews with seven informants from various medical professions and structures. The data were analyzed using a thematic analysis approach through coding, categorization, and identification of key themes. The results show that collaboration in the hospital has taken various forms, such as cross-unit coordination, communication through digital media, and regular meetings. However, the effectiveness of collaboration is still hampered by limited human resources, differences in perceptions between professions, high workloads, and variations in communication patterns. Management has implemented several strategies, such as excellent communication training, in-house training, and strengthening a patient-oriented culture, but their implementation has not been integrated into the formal collaboration system. Recommended strategies include strengthening cross-professional communication forums, team building activities, interprofessional collaboration training, employee rotation, and the development of collaboration evaluation indicators. This study concludes that management strategies play a significant role in strengthening the collaborative capabilities of medical personnel and are able to support the formation of a sustainable collaborative work culture.